A DSM Comparative Study of PTSD Incidence in Indonesia - Downs, Louis L; Rahmadian, Ahmad Ali; Noviawati, Elvi; Vakil, Goolrukh; Hendriani, Suswati; Masril, Masril; Kim, Diane (Advances in Social Sciences Research Journal, 2017)
A research project measured PTSD incidence in disaster-prone zones of Indonesia, Java six and Sumatra three years post-disaster. The Downs Posttraumatic Stress Scale, a new instrument with high reliability for children and adults (α=.94), measuring incidence of 28 identified PTSD symptoms was developed. Analysis revealed unusually high continuing incidence of PTSD. The results of analysis also compared PTSD incidence between the DSM IV-TR (24.14%) with the DSM 5 (20.1%), a significant decrease in diagnosability.